DYNAMIC SHOOTING DRILLS - Finch, Chris (Sport- és Egészségtudományi füzetek, 2025)
The main goals of these drills are learning the offensive ac-tions, taking game shots in the rhythm of the offence and reinforcing the shots that our team want to take. We must look at layups, shots at the rim and open three point shots. It is important to have in our mind, how the opponent team will play defense against our team. We have to prepare our team for the possible open shots we have to take. The pur-pose of the drills are to take uncontested layups and open threes. We do this shooting drill as muscle memories for our offence. The top criteria for decision making is spacing, mov-ing without the ball. Players must maintain good spacing, let the defence choose and the pass will be obvious.